Redox Factor-1 Inhibits Cyclooxygenase-2 Expression via Inhibiting of p38 MAPK in the A549 Cells - Yoo, Dae Goon (The Korean Physiological Society and The Korean Society of Pharmacology, 2010)
In this study, we evaluated the role of apurinic/apyrimidinic endonuclease1/redox factor-1 (Ref-1) on the tumor necrosis factor-α (TNF-α) induced cyclooxygenase-2 (COX-2) expression using A549 lung adenocarcinoma cells. TNF-α induced the expression of COX-2 in A549 cells, but did not induce BEAS-2B expression. The expression of COX-2 in A549 cells was TNF-α dose-dependent (5~100 ng/ml). TNF-α-stimulated A549 cells evidenced increased Ref-1 expression in a dose-dependent manner. The adenoviral transfection of cells with AdRef-1 inhibited TNF-α-induced COX-2 expression relative to that seen in the control cells (Adβgal). Pretreatment with 10 µM of SB203580 suppressed TNF-α-induced COX-2 expression, thereby suggesting that p38 MAPK might be involved in COX-2 expression in A549 cells. The phosphorylation of p38 MAPK was increased significantly after 5 minutes of treatment with TNF-α, reaching a maximum level at 10 min which persisted for up to 60 min. However, p38MAPK phosphorylation was markedly suppressed in the Ref-1-overexpressed A549 cells. Taken together, our results appear to indicate that Ref-1 negatively regulates COX-2 expression in response to cytokine stimulation via the inhibition of p38 MAPK phosphorylation. In the lung cancer cell lines, Ref-1 may be involved as an important negative regulator of inflammatory gene expression.